SPECTROSCOPIC INVESTIGATIONS OF GALACTIC CLUSTERS WITH ASSOCIATED CEPHEID VARIABLES. IV. COLLINDER 220 AND UW CAR - Usenko, I. A.; Kniazev, A. Yu.; Katkov, I. Yu.; Kovtyukh, V. V.; Mishenina, T. V.; Miroshnichenko, A. S.; Turner, D. G. (Одеські астрономічні публікації, 2020)
We present the results of a spectro- scopic and photometric investigation of 18 probable members of the open cluster Collinder 220, which contains the Cepheid UW Car. Besides the Cepheid, we studied tree K-giants, two B-giants, and twelve B-A-F main sequence stars. Radial velocities (RV), vsini, T eff , and logg were determined using spec- troscopic model fitting and atmosphere models. We have derived color-excesses, reddenings, and intrinsic colors for these stars using their T eff and logg from comparison to the atmosphere models, especially for hot stars. Proper motions, RV, and the GAIA DR2 2018 parallaxes allowed us to determine their membership in the cluster and absolute magnitudes. We found that seven stars along with the Cepheid can be the cluster members with a high confidence. The parallaxes and reddenings of the 7 confident cluster members led to the distances in a range of 1900–2800 pc, while the other stars are probably foreground objects. All the members have [Fe/H] near 0.1 dex. The B-giant HD90435 located near the cluster’s “turn-off” point has a low projected rotational veloc- ity, and this fact allows us to determine its chemical composition to compare with that of the Cepheid UW Car. The CNO abundances of HD90435 are nearly solar, while the Cepheid shows a deficit of carbon, an overabundance of nitrogen, a nearly solar oxygen, and an overabundance of sodium. The confident cluster member, K-supergiant CPD −57 ◦ 3199, has CNO- and Na abundances close to those of UW Car.